Age-specific reproduction in a long-lived species: the combined effects of senescence and individual quality. - McCleery, R; Perrins, C; Sheldon, B; Charmantier, A (2008)
Apparent changes in breeding performance with age measured at the population level can be due to changes in individual capacity at different ages, or to the differential survival of individuals with different capabilities. Estimating the relative importance of the two is important for understanding ageing patterns in natural populations, but there are few studies of such populations in which these effects have been disentangled. We analysed laying date and clutch size as measures of individual performance in a population of mute swans (Cygnus olor) studied over 25 years at Abbotsbury, UK. On both measures of breeding performance, individuals tended to improve up to the age of 6 or 7, and to decline after about the age of 12. Individuals with longer lifespans performed better at all ages (earlier laying, larger clutches) than animals that ceased breeding earlier. We conclude that the apparent mean increase in performance with age in mute swans is due to both individual improvement and differential survival of individuals who perform well, while the decline in older age groups is due to individual loss of function. Our results underline the need to take individual differences into account when testing hypotheses about life histories in wild populations.